CSI : Miami - Caruso, David, 1956-; Procter, Emily, 1968-; Rodriguez, Adam, 1975-; Alexander, Khandi, 1957-; Paramount Pictures Corporation; Alliance Atlantis (Firm); Jerry Bruckheimer Films; CBS Entertainment (Firm) (New York : CBS DVD ; Hollywood, Calif. : Paramount Home Entertainment, 2002)
Horatio Caine heads a group of investigators who work crimes amid the tropical surroundings and cultural crossroads of Miami. Together, the investigators collect and analyze the evidence to solve the crimes and to vindicate those who often cannot speak for themselves, the victims
Originally produced as episodes of the television program CSI : Miami in 2003 and 2004
Collective title from container
Special features : audio commentaries on select episodes ; four behind-the-scenes featurettes
David Caruso, Emily Procter, Adam Rodriguez, Khandi Alexander, Rory Cochrane
DVD ; Dolby digital 5.1 surround in English ; Dolby digital surround in Spanish ; region 1
Keywords: Criminal investigation -- Florida -- Miami -- Drama; Crime scene searches -- Miami -- Drama; Forensic sciences -- Miami -- Drama; Television programs; Forensic scientists -- Florida -- Miami -- Drama